A STUDY OF MUCOCUTANEOUS MANIFESTATIONS IN HIV-INFECTED PATIENTS PRESENTING TO A TERTIARY CARE INSTITUTE IN PUNJAB. - Naiyna Nangia; Anuradha Bhatia; Bimal Kanish; Navjot Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Human immunodeficiency virus (HIV) infection & Acquired immunodeficiency syndrome (AIDS) have been a significant public health concern worldwide with an estimated global prevalence of 40.8 million people.[1] According to latest NACO guidelines, Punjab has a high prevalence of HIV – 0.42% in 2023. Mucocutaneous diseases are common in HIV infection and they increase in frequency and severity with progression of infection and declining CD4 counts. They can function as visual markers of disease progression especially in regions with insufficient resources to test CD4 T cell counts & HIV viral load.[2–4] Being an easily assessable site for examination & biopsy, the skin can give a clue to underlying immune status, hence, evaluation of skin plays an important role in HIV infected patients. The present study was conducted to determine the pattern & prevalence of mucocutaneous manifestations in HIV positive patients and their correlation with CD4 counts in a tertiary care institute.